Pain severity and e-cigarette health literacy: the moderating role of sex - Tanya Smit; Hannah Olofsson; Pamella Nizio; Lorra Garey; Michael J Zvolensky (SAGE Publishing, 2019)
Although electronic cigarette (e-cigarette) use has increased among adults in the United States, there is still little knowledge of factors that may influence e-cigarette use or beliefs about use. Prior research suggests that health literacy plays an important role in e-cigarette beliefs, including perceived benefits and risks of e-cigarette use, as well as e-cigarette dependence. Yet, limited work has examined risk factors of poor e-cigarette health literacy. From a biopsychological perspective, sex and pain severity represent two constructs that may impact e-cigarette health literacy. To date, however, no research has investigated differences in e-cigarette health literacy across pain, sex, or their interrelation. Thus, the present study was conducted to evaluate the interactive effect of pain severity and sex on e-cigarette health literacy. Participants included 319 current, adult e-cigarette users (60.5% female, M age  = 36.82 years, SD =  10.62). Findings supported a significant pain by sex interaction, such that pain related to e-cigarette health literacy among women ( b =  .10, SE  = .03, P  < .001), but not men ( b =  .01, SE  = .03, P  = .60). The present findings suggest that pain may uniquely impact the degree to which women, but not men, seek and understand information on e-cigarettes.